Enhancing Seaweed-Based Dodol Production in Coastal Communities: A Case Study of Gracillaria verrucosa in Wisata Bahari Tlocor, Indonesia - Lukman Hudi; Rahmah Utami Budiandari; Andriani Eko Prihatiningrum (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents a case study on the development and implementation of a training program aimed at enhancing the production of seaweed-based dodol in Tlocor Kedungpandan Jabon Hamlet, Indonesia. Gracillaria verrucosa, an agar-producing red algae, holds promising potential for cultivation alongside shrimp and milkfish rearing. The study utilized a survey to assess the area's potential, engaged with local communities to identify challenges, and designed a training program accordingly. The training involved demonstrations and guidance on seaweed processing, handling, packaging, and marketing. The goal was to empower the community to produce high-quality seaweed dodol as a form of Small and Medium Enterprises (SMEs) and provide unique local products for Wisata Bahari Tlocor, the tourist destination. The results demonstrated that with proper training and support, the community could independently produce quality seaweed dodol, thereby increasing their socio-economic well-being. The findings suggest the need for continued support in product development, packaging, marketing, licensing, and capital investment to fully leverage the potential of seaweed-based products in the region. This study highlights the significance of community-based initiatives in promoting sustainable economic growth and preserving local culinary heritage through seaweed-based dodol production. Highlight: Potential of Gracillaria verrucosa: This study explores the untapped potential of Gracillaria verrucosa seaweed as a valuable resource in aquaculture and as a basis for high-value processed products. Dodol Production and Economic Value: The research emphasizes the importance of developing seaweed processing techniques to create